Targeting E3 ubiquitin ligases: a new frontier in idiopathic pulmonary fibrosis treatment - Zhang, Kun; Yuan, Hui; Shi, Lin (Frontiers in Immunology, 2025)
Ubiquitination is a modification prevalent in eukaryotic cells. Disruptions in ubiquitination processes can have detrimental effects, potentially leading to diseases that endanger life. E3 ubiquitin ligases specifically recognize substrate proteins during ubiquitin modification, regulating intracellular protein levels and functions through the ubiquitin-proteasome pathway or TGF-β signal transduction. In recent years, substantial evidence has emerged, emphasizing the pivotal role that E3 ubiquitin ligases play in the development of pulmonary fibrosis. Advancing our understanding of how E3 ubiquitin ligases interact with pulmonary fibrosis could reveal new therapeutic targets and treatments for idiopathic pulmonary fibrosis (IPF), as well as innovative approaches in diagnosis and therapy. This review explores known regulatory mechanisms and identifies E3 ligases that have been implicated in IPF development.